Manajemen dan Peran Bursa Kerja Khusus dalam Pengenalan dan Pengembangan Karier Siswa di SMKN 2 Jiwan - Hidayati, Khusnul (Indonesian Journal of Learning and Instructional Innovation, 2023)
This research aims to provide a detailed description of the Special Job Market (BKK)  management  in facilitating the placement of vocational high school (SMK)  graduates  into  the workforce.The approach used in  this  research  is a qualitative descriptive  approach.The study was  conducted at  SMKN  2  Jiwan, Madiun  Regency. Data were  collected through a series of methods,including interviews, observations, and  document  analysis.The management of the Special Job Market (BKK) at SMKN 2 Jiwan is  carried  out in four stages: planning, organizing, implementing, and controlling.In the planning  stage, the steps taken include surveys of  relevant business and industry partners,  coordination  meetings  with  the  BKK  team,  the  signing  of  a  Memorandum  of  Understanding between the vocational school (SMK) and business partners, as well as  the implementation of career guidance and alumni tracking.The organizing stage  involves the coordination of  BKK administrators  in  collaboration with  the  Vice  Principal for Public Relations.The implementation stage encompasses the signing of  the  MoU,the execution of workforce recruitment processes, career guidance related to  recruitment, and the execution of  alumni tracking (tracer  istudy).The final  stage is controlling, involving monitoring and auditing, both internally  and  externally.  The results of the control demonstrate that the BKK has been operating optimally,  although there are still some aspects that need improvement for future  programs.Penelitian  ini  bertujuan   untuk  memberikan  deskripsi  terperinci  mengenai  manajemen  Bursa  Kerja  Khusus  (BKK)  dalam  memfasilitasi  penyaluran  lulusan  SMK  ke  dunia  kerja.  Pendekatan  yang  digunakan  dalam  penelitian  ni  adalah  pendekatan  deskriptif  kualitatif.  Penelitian ini  dilakukan  di  SMKN  2  Jiwan,  Kabupaten  Madiun.  Data  dikumpulkan  melalui  serangkaian  metode,  termasuk  wawancara,  observasi,  serta  analisis  dokumen.  Manajemen  Bursa  Kerja  Khusus  (BKK)  di  SMKN  2  Jiwan dijalankan melalui empat tahapan: merencanakan,  mengorganisasikan, melaksanakan,dan mengendalikan.Pada tahap  merencanakan,  langkah-langkah yang dilakukan yaitu survei terhadap  berbagai IDUKA yang relevan,rapat koordinasi dengan tim BKK,  penandatanganan Memorandum of Understanding antara SMK dan IDUKA,  serta pelaksanaan pembimbingan karir dan penelusuran lulusan.Tahap  pengorganisasian  melibatkan  pengurus  BKK  dengan  berkoordinasi  Wakil  Kepala Sekolah Bidang Humas.Tahap melaksanakan mencakup  penandatanganan MoU, pelaksanaan proses rekrutmen tenaga kerja,  bimbingan karir terkait rekrutmen,dan pelaksanaan penelusuran lulusan  (tracer  study).Tahap akhir adalah mengendalikan, mengawasi dan  mengaudit,  baik  secara  nternal  maupun  eksternal.  Hasil  dari  penelitian  adalah  manajemen  BKK  SMKN  2  Jiwan  berjalan  dengan  optimal  meskipun  masih  ada  beberapa  aspek  yang  perlu  ditingkatan  untuk  program-program